Acid Rain - Turck, Mary. (New York : Crestwood House, 1990)
Discusses the sources, destructive effects, and future control of acid rain.
Includes bibliographical references (p. 43) and index.
Keywords: Acid rain -- Environmental aspects; Acid rain -- Environmental aspects -- United States; Acid rain